Identification and characterization of extrachromosomal circular DNA in alcohol induced osteonecrosis of femoral head - Zhou, Tingting; Ma, Shiqiang; Zhao, Yunchao; Guo, Donghui; Wang, Hengjun; Kuang, Mingjie; Li, Xiaoming (Frontiers in Genetics, 2022)
Alcohol-induced osteonecrosis of the femoral head (AIONFH) is a complicated refractory bone disease seen in the clinic. The pathogenesis of AIONFH is still controversial. Extrachromosomal circular DNA (eccDNA) elements have beenindicated ubiquitously exist in eukaryotic genomes. However, the characteristics and biological functions of eccDNAs remain unclear in AIONFH. In this study, eccDNAs from AIONFH samples (n=7) and fracture of femoral neck samples as a control (n=7) were purified by removing linear DNA and rolling circle amplification. High-throughput sequencing and bioinformatics analysis were performed to study the characterization and biofunction of eccDNAs. We identified more than 600,000 unique eccDNAs. The number of detected eccDNAs in AIONFH was less than that in the control, and eccDNA formation may be related to transcription or other characteristics of coding genes. The eccDNA lengths are mainly distributed between 0.1 kb and 1 kb, with a major peak in 0.358 kb. The bioinformatic analysis showed that 25 significant genes were detected, including MAP3K1, ADCY1, and CACNA1S MACF1, which contributed to regulating bone formation. GO and KEGG analyses suggested that the related genes derived from exons mainly affected metabolic processes and signal transduction, and bone metabolism-related pathways, such as the MAPK pathway and TGF-β pathway, were enriched. EccDNAs in AIONFH are common and may play an important role in pathogenesis by regulating bone metabolism.